2018
DOI: 10.1088/1367-2630/aa9298
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain imaging of gigahertz surface waves on an acoustic metamaterial

Abstract: We extend time-domain imaging in acoustic metamaterials to gigahertz frequencies. Using a sample consisting of a regular array of ∼1 μm diameter silica microspheres forming a two-dimensional triangular lattice on a substrate, we implement an ultrafast technique to probe surface acoustic wave propagation inside the metamaterial area and incident on the metamaterial from a region containing no microspheres, which reveals the acoustic metamaterial dispersion, the presence of band gaps and the acoustic transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…Minor changes are introduced along the other directions due to the different unit-cell periodicity. In addition, we believe that a similar tuning paradigm could be implemented at the microscale and nanoscale, where contact-based metamaterials made of micro-and nanobeads deposited on a silica substrate have already been utilized to filter SAWs in the rf regime [12][13][14]. Within this context, resonance tuning via a magnetic field could be achieved by employing, for example, magnetic microbeads, similar to those already commercialized for magnetic separation techniques [42], and modulating their contact resonances via an external magnetic field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor changes are introduced along the other directions due to the different unit-cell periodicity. In addition, we believe that a similar tuning paradigm could be implemented at the microscale and nanoscale, where contact-based metamaterials made of micro-and nanobeads deposited on a silica substrate have already been utilized to filter SAWs in the rf regime [12][13][14]. Within this context, resonance tuning via a magnetic field could be achieved by employing, for example, magnetic microbeads, similar to those already commercialized for magnetic separation techniques [42], and modulating their contact resonances via an external magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…The same hybridization phenomenon is observed when SAWs interact with a granular layer of silica microbeads, owing to the contact resonance of each sphere adhered to the elastic substrate. These granular metamaterials have been thoroughly investigated with the goal of understanding the microbeads' * antonio.palermo6@unibo.it contact dynamics [12,13] and to realize SAW filters in the megahertz and gigahertz range [14].…”
Section: Introductionmentioning
confidence: 99%
“…[157] Another self-assembly method is the wedgeshaped cell convective technique, implemented to build an AMM for gigahertz imaging capabilities, also exploiting contact mechanics ( Figure 7d). [149] These examples show how self-assembly techniques can transform random colloidal dispersions into functional AMMs or PCs for acoustic applications.…”
Section: Arrangement and Assembly Methodsmentioning
confidence: 99%
“…The third strategy enabling the modification of SAWs dispersion is based on the nanoparticle–substrate contact resonance. This effect was first investigated in the sub‐gigahertz regime by the pump‐probe transient grating (TG) technique and time‐domain imaging in PnCs made out of self‐assembled silica microspheres adhered to an aluminium‐coated glass substrate. Recent follow up of the TG study has revealed additional features in the gigahertz range such as contact‐induced splitting of the vibrational modes of nanoparticles and the interaction of these modes with Rayleigh SAWs .…”
Section: Surface and Membrane Hypersonic 2d Pncsmentioning
confidence: 99%